Application of microbial inoculants significantly enhances crop productivity: A meta‐analysis of studies from 2010 to 2020. Issue 3 (27th August 2022) - Li, Jiayu; Wang, Juntao; Liu, Hongwei; Macdonald, Catriona A.; Singh, Brajesh K.
Abstract: Introduction: With the rapid development of microbial technology, microbial inoculant is considered as a promising tool in sustainable agricultural systems. Mechanisms by which microbial inoculants improve crop yield include improving plant nutrient availability and alleviating abiotic/biotic stresses (e.g., drought, salt and disease). However, the field efficacy of microbial inoculants remains inconsistent, which constrains large‐scale adoptions. Identity of dominant mechanisms that underpin the positive impacts of different microbial inoculants is limited. Thus, a comprehensive quantitative assessment of known inoculants on crop performance is needed to provide guidance for the development of effective microbial tools from both research and commercial perspectives. Materials and Methods: Based on 97 peer‐reviewed publications, we conducted a meta‐analysis to quantify the benefits of different microbial inoculants on crop yield, and to identify the key mechanisms that underpin enhanced crop yield. Results: Result showed that (i) alleviation of stresses was the major mechanism (53.95%, n = 53) by which microbial inoculants enhance crop yield, while improving plant nutrient availability accounted for 22.25% ( n = 58) of crop yield enhancement. (ii) Pseudomonas was the most effective microbial inoculant in enhancing crop yield through alleviating stresses (63.91%, n = 15), whereas Enterobacter was the most effective in improving plant nutrient availability (27.12%, n = 5). (iii) Considering both mechanisms together, Pseudomonas (49.94%, n = 21), Enterobacter (27.55%, n = 13) and Bacillus (25.66%, n = 32) were the largest sources of microbial inoculants to enhance crop yield, and the combination of diazotroph Burkholderia with its legume host had the highest effect on improving the yield (by 196.38%). Microbial inoculants also improve nutritional quality by enhancing mineral contents in the produce. Conclusion: Our analysis provides evidence that microbial inoculants can enhance agricultural productivity and nutritional quality and can be used either alone or in combination with reduced amount of agrochemicals to promote sustainable agriculture. Abstract : The application of microbial inoculants increase crop yields similar to use to conventional farming using synthetic fertilisers.